The Impacts Of Malaysian Foreign Policy During Tun Mahathir's Era Towards Palestine - Abdul Majid Hafiz, Mohamed; Murshamshul Kamariah, Musa; Ahmad Sharif, Haron; Mohd Afandi, Salleh; Abdullahi Ayoade, Ahmad (2017)
During the tenure of Mahathir Mohammed as Prime Minister, the Palestine issue was made a special cause to Malaysia. It was during Mahathir's administration that the government and the country became highly committed to helping to bring world attention to and to resolving the Palestine-Israel crisis. This paper discusses the impact of Malaysia's involvement in the Palestine cause during Mahathir's era and highlights the impact it had on Palestine, Mahathir as Prime Minister and Malaysia as a whole. Malaysia's pro-Palestine cause has helped the world gain in awareness of the Palestine issue; nevertheless, the conflict in Palestine continues, showing no sign of ending.